Determinación del índice de área foliar y fracción de radiación fotosintéticamente activa en el Bosque Húmedo La Esperanza – La Maná, mediante metodologías óptic - Zapata Tello, Wilson Marcelo (2017)
During the last few centuries a series of changes in the climatic conditions generated on the planet have been observed, a phenomenon that has been called "global climate change." One of the causes is the limitation, to maintain a carbon balance in tropical humid forests and Subtropical due to the relationship of radiation and vegetarían would be less time consuming cheira maximum photosynthesis.The problem is framed in the absence of information mor the decision maquino in environmental care and the lack of measures and policies oriented to the Conservarían of ecosystems.This is due in part to insufficient scientific technical information on the application of optical methods and canopy geometry in the determination of climatically essential variables of wet forests.We will apply optical methodologies for the characterization of essential variables For the quality of the climate in local conditions. For this, analog instrumentation was designed for hemispheric imaging. Mathematical models were applied to determine the close relationship between the leaf area index and the fraction of photosynthetically active radiation. There is a foliar area of 3.05 square meters of vegetation per square meter of surface that absorbs 29.7 mol per day of radiation and captures 32 kg of CO2 per square meter annually. These results indicare that wet forest is one of the most productive ecosystems that contribute to mitigating climate change